Developing Canva-Assisted Problem-Based Learning Worksheets for Cultural Diversity Learning in Elementary Schools - Izzatul Janna; Nurdin Kaso; Ervi Rahmadani (Journal of Indonesian Islamic Studies, 2025)
This study aimed to develop and evaluate the validity and practicality of Canva-assisted Problem-Based Learning (PBL) student worksheets (LKPD) for cultural diversity materials in fourth-grade IPAS learning at SDN 207 Pembuniang, North Luwu Regency. This research employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research subjects involved seven fourth-grade students, one classroom teacher, and three expert validators consisting of a material expert, a language expert, and a design expert. Data were collected through observations, interviews, questionnaires, and documentation and analyzed using descriptive qualitative and quantitative techniques. The results showed that the developed worksheets achieved a high level of validity based on expert assessments, including material expert validation at 89.2% categorized as very valid, language expert validation at 79.5% categorized as valid, and design expert validation at 75% categorized as valid. Furthermore, the practicality test demonstrated very practical results, with student responses reaching 93.8% and teacher responses 85.5%. The findings indicate that the Canva-assisted PBL worksheets are feasible and practical for supporting interactive and student-centered learning in elementary school IPAS subjects. The novelty of this study lies in the integration of Canva-assisted visual design with the Problem-Based Learning approach to develop contextual and visually engaging worksheets that support students’ participation, motivation, and problem-solving skills in cultural diversity learning.